Reduced protein diet and amino acid concentration alter intestinal barrier function and performance of broiler chickens with or without synthetic glucocorticoid. (28th December 2018) - Barekatain, R; Nattrass, G; Tilbrook, A J; Chousalkar, K; Gilani, S
ABSTRACT: Little is known about the effect of low-protein (LP) diets on intestinal barrier function and permeability. In the first part of this study, starting on day 9 of age, the growth performance of the birds fed 3 experimental diets in each phase of feeding (G/F: grower/finisher) was investigated. Three experimental diets were as follows: LP (170/150 g/kg CP) fortified with essential amino acids (EAA), standard protein (SP), (202/190 g/kg), and high protein (HP) (220/210 g/kg). LP and SP diets contained a similar level of EAA concentration, while the HP diet contained 10% above the Ross 308 specifications. Each diet was replicated 6 times (10 male birds per replicate). The second part investigated intestinal permeability (IP) and function on additional 72 birds. On days 14, 16, and 20, a total of 36 birds (12 birds per diet) were injected with dexamethasone (DEX) to induce leaky gut. Birds fed LP diets had lower body weight gain (BWG) and higher feed conversion ratio (FCR) compared with SP and HP diets in both grower and finisher phases of feeding. For the challenge part, DEX increased the FCR independent of diets. Diet and DEX interacted for BWG, whereby the effect of diets was only evident in sham-injected birds. Birds fed LP had a higher fluorescein isothiocyanate dextran (FITC-d) concentration indicating a more permeable intestine compared to HP, but similar to SP. DEX increased FITC-d concentration in all dietary treatments. Birds fed LP had less ileal zonula occludens-2 (ZO-2) expression in comparison with SP, but not HP. DEX increased the expression of Claudin3 and ZO-2 and reduced Claudin1 ( P < 0.05) and junctional adhesion molecule 2 in the ileum. Expression of ileal Na + -dependent glucose transporter 1 (SGLT1) was upregulated in LP fed group. It is concluded that compared with SP, IP can be maintained in LP by supplementing EAA. However, when compared with HP, feeding birds with LP may lead to a higher IP. DEX had a profound independent effect on intestinal barrier function.